A Growing Inflammatory Mass of Gastrosplenic Ligament Mimicking Recurrent Colon Cancer on FDG PET/CT. (July 2021) - Shen, Guohua; Wang, Rang; Kuang, Anren
Abstract : Abstract: A 64-year-old man diagnosed with colon cancer underwent left hemicolectomy 1 year ago. The postoperative pathological stage was T4a N0 M0. Serial follow-up CT scans revealed a growing soft-tissue mass in the gastrosplenic ligament. FDG PET/CT was then performed for further restaging, and intense FDG uptake was observed inside the lesion, whereas no other abnormal uptake was seen. A solitary recurrence was suspected, and he underwent surgical resection. Histopathologic findings confirmed the diagnosis of chronic inflammation. This case demonstrates how a growing FDG-avid inflammatory mass of surgical site could easily be mistaken for recurrence.